PERLINDUNGAN HUKUM TERHADAP WARGA NEGARA INDONESIA NON-PRIBUMI UNTUK MEMPEROLEH KEPASTIAN HAK MILIK - Listya Irawan, Riza Anggun (Jurnal Cakrawala Hukum, 2016)
The ownership of the land ownership in Yogyakarta City is different from other regions because of the implementation of the 1975 DIY Regional Head Instruction on Uniform Policy of Land Rights Provision to a NonIndigenous Indonesian Citizen. As a result Citizens of Chinese descendants residing in the city of Yogyakarta cannot have ownership rights to the land and it is contrary to the principle of nationality in the UUPA which asserts that all citizens can have ownership rights to land in Indonesia without discriminating one’s race or ethnicity. The research method used is empirical juridical research. The dominant factor underlying the difficulties of Chinese citizenship to own property rights to land is caused by the factor of Legal Culture in Yogyakarta City. Prohibition of granting property rights to land for Chinese Citizens resulted in impediments in the implementation of rights and obligations to be performed. Regulations that allow citizens of Chinese descent to be able to own land rights in Yogyakarta City but with restrictions such as the area of land that can be purchased.